2004
DOI: 10.1111/j.1467-2494.2004.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical niacinamide reduces yellowing, wrinkling, red blotchiness, and hyperpigmented spots in aging facial skin1

Abstract: Previous clinical testing of topical niacinamide (vitamin B3) has revealed a broad array of improvements in the appearance of aging facial skin. The study reported here was done to confirm some of those previous observations and to evaluate additional end points such as skin anti-yellowing. Caucasian female subjects (n = 50, aged 40-60 years) participated in a 12-week, double-blind, placebo-controlled, split-face, left-right randomized clinical study assessing two topical products: moisturizer control product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 33 publications
1
120
0
5
Order By: Relevance
“…Dark-skinned Yucatan swine treated with resveratrol showed visible skin lightening, which was confirmed histologically [79] Glabiridin (Liquirice) Glabrene and isoliquiritigenin in the licorice extract can inhibit both mono-and diphenolase tyrosinase activities [81] Trial for melasma treatment using liquritin cream showed good to excellent results in 90% of the patients [137] Soyabean Soyabean inhibits protease-activated receptor 2 cleavage, affects cytoskeletal and cell surface organization, and reduces keratino cyte phagocytosis [88] Study on facial photodamage showed that soyabean is more efficient than the vehicle in improving mottled pigmentation [89] Niacinamide No catalytic activity of mushroom tyrosinase or on melanogenesis in monocultures of melanocytes. 35-68% inhibition of melanosome transfer in the coculture model [91] Clinical study showed significant improvements versus control in end points: fine lines/wrinkles, hyperpigmentation spots, texture, and red blotchiness [92] …”
Section: Aloesinmentioning
confidence: 99%
“…Dark-skinned Yucatan swine treated with resveratrol showed visible skin lightening, which was confirmed histologically [79] Glabiridin (Liquirice) Glabrene and isoliquiritigenin in the licorice extract can inhibit both mono-and diphenolase tyrosinase activities [81] Trial for melasma treatment using liquritin cream showed good to excellent results in 90% of the patients [137] Soyabean Soyabean inhibits protease-activated receptor 2 cleavage, affects cytoskeletal and cell surface organization, and reduces keratino cyte phagocytosis [88] Study on facial photodamage showed that soyabean is more efficient than the vehicle in improving mottled pigmentation [89] Niacinamide No catalytic activity of mushroom tyrosinase or on melanogenesis in monocultures of melanocytes. 35-68% inhibition of melanosome transfer in the coculture model [91] Clinical study showed significant improvements versus control in end points: fine lines/wrinkles, hyperpigmentation spots, texture, and red blotchiness [92] …”
Section: Aloesinmentioning
confidence: 99%
“…Retinoller, peptidler ve büyüme faktörleri gibi hücre düzenleyiciler ise; kollajen metabolizması üzerinde doğrudan etkilidirler ve kollajen üretimini arttırırlar. Vitamin C, B3 ve E küçük molekül ağırlıklarından dolayı hücreye kolaylıkla penetre olabilen önemli antioksidan maddelerdir 37 . Vitamin C % 5-15 konsantrasyonlarında yaşlanma karşıtı olarak kullanılmaktadır.…”
Section: Kollajen Ve Elastin Ile Bu Yapıları Destekleyen Bileşenlerunclassified
“…Vitamin B3, %5 konsantrasyonda yaşlanma karşıtı olarak kullanılmaktadır 40 . Cilt elastikliği, eritemi ve pigmentasyonu üzerinde etkili olduğu görülmüştür 37,38,41 . Vitamin E % 2-20 konsantrasyonlarında kullanılmaktadır.…”
Section: Kollajen Ve Elastin Ile Bu Yapıları Destekleyen Bileşenlerunclassified
“…Research also suggests that niacinamide may decrease melanogenesis by interfering with the interaction between keratinocytes and melanocytes but not through a directly inhibitory effect on melanocytes. Two to five percent niacinamide has proven to be an effective lightening agent for patients with melasma or UV induced hyperpigmentation [27][28][29]; however, studies are needed to determine its safety and efficacy in the treatment of PIH.…”
Section: Niacinamidementioning
confidence: 99%